A Small Temperate Lake in the 21st Century: Dynamics of Water Temperature, Ice Phenology, Dissolved Oxygen, and Chlorophyll a. Issue 7 (10th July 2018) - Tan, Zeli; Yao, Huaxia; Zhuang, Qianlai
Abstract: It is unclear how small temperate lakes will evolve physically and biologically in the whole water column under future climate because previous modeling studies usually focused on only one or two physical or biological state variables in the surface waters. Here we used a well‐validated lake biogeochemistry model driven by different climate scenarios of the 21st century to predict the dynamics of ice phenology, water temperature, dissolved oxygen (DO), and chlorophyll a in a small Canadian temperate lake (0.714 km 2 ) that is oligotrophic and strongly stratified in summer, considering the influence of catchment hydrology. The ice season and thickness of the lake are projected to shrink substantially under warming, resulting in a positive energy feedback between climate and the lake. Due to the reduced heat diffusion and water mixing, the dynamics of water temperature in surface and deep waters of the lake are considerably different, with surface waters warmed dramatically but deep waters muted to warming. DO depletion is predicted to occur in the whole water column of the lake under warming, but the controlling processes are depth dependent. Unexpectedly, the predicted growth of the lake's chlorophyll a is small under warming, due to the weakened convection and the mismatch of the timings of favorable solar radiation, thermal, and nutrient conditions. For the examined state variables, our prediction shows that only the dynamics of DO is significantly impacted by the changing catchment hydrology. This study suggests that similar temperate lakes will have diverse physical and biological responses to climate change. Plain Language Summary: Understanding the influence of climate change on the physical and biological states of small temperate lakes is important given their landscape's abundance on the Earth surface. Using a well‐validated lake biogeochemistry model, the dynamics of ice thickness, water temperature, dissolved oxygen, and chlorophyll a during the 21st century was simulated for a small temperate lake that is nutrient poor and seasonally ice‐covered and experiences strong temperature stratification in summer. The model predicts that the lake would change dramatically under intense warming, including the occurrence of ice‐free years and severe depletion of dissolved oxygen in the surface and deep waters. The model also predicts that chlorophyll a in the lake, a negative factor for water quality, would not increase rapidly under climate warming. This study highlights the importance to study small temperate lakes using complex lake biogeochemistry models that can simulate diverse lake processes and their interactions. Key Points: Small temperate lakes that are oligotrophic and strongly stratified in summer are sensitive to climate change The dynamics of water temperature and dissolved oxygen in these small temperate lakes are depth dependent under climate change Climate warming will not drive large growth of chlorophyll a in these lakes, due to the timing mismatch between energy and nutrient optima